Determination of Antidepressants in Human Plasma by Modified Cloud-Point Extraction Coupled with Mass Spectrometry - Elżbieta Gniazdowska; Natalia Korytowska; Grzegorz Kłudka; Joanna Giebułtowicz (MDPI AG, 2020)
Cloud-point extraction (CPE) is rarely combined with liquid chromatography coupled to mass spectrometry (LC-MS) in drug determination due to the matrix effect (ME). However, we have recently shown that ME is not a limiting factor in CPE. Low extraction efficiency may be improved by salt addition, but none of the salts used in CPE are suitable for LC-MS. It is the first time that the influences of a volatile salt-ammonium acetate (AA)-on the CPE extraction efficiency and ME have been studied. Our modification of CPE included also the use of ethanol instead of acetonitrile to reduce the sample viscosity and make the method more environmentally friendly. We developed and validated CPE-LC-MS for the simultaneous determination of 21 antidepressants in plasma that can be useful for clinical and forensic toxicology. The selected parameters included Triton X-114 concentration (1.5 and 6%, w/v), concentration of AA (0, 10, 20 and 30%, w/v), and pH (3.5, 6.8 and 10.2). The addition of 10% of AA increased recovery twice. For 20 and 30% (w/v) of AA, three phases were formed that prolonged the extraction process. The developed CPE method (6% Triton X-114, 10% AA, pH 10.2) was successfully validated through LC-MS/MS simultaneous determination of 21 antidepressants in human plasma. The linearity was in the range of 10-750 ng/mL (r2 > 0.990).